Evaluating the key findings of Image Fusion Techniques (International Journal of Engineering and Computer Science, 2014)
An objective of digital image fusion combine two or more source images to get a single digital image known as fused image. This fused image will be more informative for human as well as machine also. We can used the different methods of fusion has been proposed in literature both in spatial domain and wavelet domain. This paper will be propose a pixel level image fusion using multiresolution (BWT). The two more methods we can use in this paper is DCT and PCA. PCA based on fusion and sharpness of fused image. PCA performance evalution of proposed method used matric like: fusion factor, entropy, standard deviation, to get the better results. DCT will be suitable and time saving in real time system for fusion of multifocus images based on variance calculation.